The black book [compact disc, unabridged] - Patterson, James, 1947- (Hachette Audio, 2017)
Left for dead alongside his tempestuous former partner and a hard-charging assistant district attorney out for blood, Billy Harney miraculously survives. He remembers nothing about the events leading up to the shootout. Charged with double murder and desperate to clear his name, Billy retraces his steps to get to the bottom of what happened. When he discovers the existence of a little black book that everyone who's anyone in Chicago will stop at nothing to get their hands on, Billy suspects it contains the truth that will either set him free or confirm his worst fears.